Rate Regulation, Competition, and Loss Reserve Discounting by Property-Casualty Insurers - Nelson, Karen K. (The Accounting Review, 2000)
This study examines whether the reported loss reserves of property-casualty insurers contain an implicit discount for the time value of money. Reporting the present value of loss reserves enables insurers to justify the competitive level of insurance premiums to regulators. The evidence indicates that there is a positive and significant discount rate implicit in the relation between reported loss reserves and expected future claim payments. Moreover, insurers subject to relatively stringent rate regulation discount to a greater extent than do other insurers. The results also suggest that implicit discounting is distinct from solvency and tax motives to exercise discretion over the loss reserve.